2022
DOI: 10.1101/2022.08.18.504412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are Deep Learning Structural Models Sufficiently Accurate for Virtual Screening? Application of Docking Algorithms to AlphaFold2 Predicted Structures

Abstract: Machine learning protein structure prediction, such as RosettaFold and AlphaFold2, have impacted the structural biology field, raising a fair amount of discussion around its potential role in drug discovery. While we find some preliminary studies addressing the usage of these models in virtual screening, none of them focus on the prospect of hit-finding in a real-world virtual screen with a target with low sequence identity. In order to address this, we have developed an AlphaFiold2 version where we exclude al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…While all data produced here were obtained without any user intervention, and as such, it is likely that model quality can be improved through customization of sequence alignment and model building parameters, there is clearly a large gap between AF2 and the methods compared to here (as seen already in the recent CASP competitions) . Still, many studies have shown limitations when modeling structures with AF2, including erroneous predictions for highly disordered structures, bias toward a particular conformational state, or the tendency to collapse potential binding sites. , …”
Section: Discussionmentioning
confidence: 99%
“…While all data produced here were obtained without any user intervention, and as such, it is likely that model quality can be improved through customization of sequence alignment and model building parameters, there is clearly a large gap between AF2 and the methods compared to here (as seen already in the recent CASP competitions) . Still, many studies have shown limitations when modeling structures with AF2, including erroneous predictions for highly disordered structures, bias toward a particular conformational state, or the tendency to collapse potential binding sites. , …”
Section: Discussionmentioning
confidence: 99%
“…(Saldanõ et al, 2022) Docking efforts against AlphaFold structures show lower performance than against holo structures available on the PDB. (Díaz-Rovira et al, 2022; Wong et al, 2022) Here, we show that this can be mitigated by considering conformational heterogeneity using MSMs. Using a highly flexible system, we can sample conformations and identify cryptic pockets that can be successfully used in downstream virtual screening applications.…”
Section: Discussionmentioning
confidence: 92%
“…52 More sophisticated methods, like free energy perturbation (FEP) combined with AlphaFold2 homology models, were demonstrated to achieve accurate results recently. 53 However, the requirement of a correct binding mode for those calculations was also achieved by aligned ligand poses from crystal structures and refinement to resolve "significant clashes in some cases". We hence conclude that for a prospective virtual screening by molecular docking, multiple programs and homology models and surrogate structures should be considered and validated using known ligands if these are available.…”
Section: ■ Resultsmentioning
confidence: 99%
“…However, even though docking with experimental structures (“control”) showed slightly better results than homology models, observed ROC AUCs (average 0.67/67, median 0.74/69 for FlexX/FRED) and adjusted log AUCs (average 0.13/0.15, median 0.14/0.13 for FlexX/FRED) are not ideal, and current molecular docking software might not yet be able to take advantage of the potentially high accuracy of, for example, MD-refined and ligand-steered AlphaFold2 homology models . More sophisticated methods, like free energy perturbation (FEP) combined with AlphaFold2 homology models, were demonstrated to achieve accurate results recently . However, the requirement of a correct binding mode for those calculations was also achieved by aligned ligand poses from crystal structures and refinement to resolve “significant clashes in some cases”.…”
Section: Discussionmentioning
confidence: 99%